Higher Order Thinking Skills Of Reading Exercises In English Textbook “Bahasa Inggris: Work In Progress” Based On Revised Bloom’s Taxonomy - Husni, Sofia Silvia; Ginting, Siti Aisah (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2023)
This study aims to find out the application of higher order thinking skills in reading exercises questions in the textbook entitled Bahasa Inggris: Work in Progress Grade X that released by Kemendikbud RI in 2022, which implemented Kurikulum Merdeka is English book that beneficial in train Senior High School students grade tenth. In this textbook contained 55 reading questions in total. There were 30 or 54,54% reading questions that tested students' ability to think in higher order. Additionally, 25 or 45,45% reading exercise questions that tested students' lower-order thinking abilities. Despite being one of the most up-to-date textbooks currently used in the curriculum, this book already fulfils the distribution of higher-order thinking exercises. Using this Bloom’s Taxonomy especially revised, this research has improved HOTS in those practice because learners need in develop their critical thinking skills and capabilities to analyse, evaluate, and then create something that is beneficial in era of globalization.